Marta Díaz-Zorita Bonilla. The Copper Age in South-West Spain. A bioarchaeological approach to prehistoric social organization. - Silva, Ana María (SPAL - Revista de Prehistoria y Arqueología, 2019)
Marta Díaz-Zorita Bonilla. The Copper Age in South-West Spain. A bioarchaeological approach to prehistoric social organization. BAR International Series 2840. Oxford, Archaeopress, 2017. ISBN 978 1 4073 1509 6.